(untitled) (Annals of Medical Research, 2021)
Aim: Feeding difficulties are common in typically developing children and the prevalence ranges from 25% to 45%. Although using an assessment tool is the best approach when planning an intervention, assessment of feeding disorders is mostly accomplished by informal parent interviews in clinical practice. This study was designed to assess the mealtime behaviours of young children with ‘Feeding Difficulties’ (FD) by an instrument and to compare the results with ‘Typically Developing’ (TD) children.Material and Methods: A total of 61 children with FDs and 63 TD children aged 6-42 months were included. The Behavioral Pediatric Feeding Assessment Scale (BPFAS) was completed to describe the child’s feeding behaviors and the parents’ mealtime strategies. Results:FD group had higher scores than TD group in all BPFAS subtests’ scores. The mean ‘Total Frequency Score’ was 104.6 in FD group whereas 72.9 in TD group (p=0.0001). The FD group had more problematic feeding behaviours in comparison to TD group. The mean ‘Total Problem Score’ of TD group was 6.1 whereas 20.1 in children with FD (p=0.0001).Conclusion: This study supports the BPFAS to be a useful and practical feeding assessment tool and also has the advantage of incorporating parents’ feelings about child’s feeding behaviors.